Pemanfaatan Internet Of Things dalam Sistem Smart Garden Untuk Kontrol dan Monitoring Tanaman - Firmansyah, Wahyu; Rosyidi, Lukman; Munir, Sirojul (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
Gardening is now a popular hobby and healthy lifestyle trend in Indonesia. However, traditional gardening methods often require a lot of time, effort, and large areas of land, thus deterring many people from growing crops. This research aims to design and develop an efficient and easy-to-use automatic watering system for home gardens by utilizing IoT technology. The method used is Research and Development (R&D) to produce and test the effectiveness of the product. The system is built using ESP8266, a DHT11 sensor to measure air temperature and humidity, and a soil moisture sensor to measure soil moisture. The system has two modes of operation: automatic and manual. In manual mode, users can control the pump through the Blynk app. The test results show that the developed Smart Garden system can control and measure soil moisture levels through the Blynk platform with a success rate of 100%. In addition, it is recommended for further research to add a manual system on the device to overcome the problem if the WIFI connection is lost.